Prevalência e fatores associados a enteroparasitoses em pacientes portadores de urticária crônica - Sá, Náiade Maria Rêgo Silva de (2023)
Enteroparasitoses represent an important public health problem, since these diseases occur predominantly in areas where the population's living conditions are precarious, and are considered neglected diseases. They have a high prevalence, especially in developing countries where, alongside the environmental conditions that facilitate their occurrence, there are economic, social and cultural factors that are highly relevant to their widespread dissemination. Chronic urticaria is a condition characterized by the appearance of skin rashes and/or angioedema lasting longer than 6 weeks. The most recent guideline on urticaria considers parasitic infections as possible underlying causes of this disorder. Although this association has been discussed for several years, there is still a relative scarcity of studies evaluating the prevalence of parasitic infection and chronic urticaria, especially in underdeveloped countries such as Brazil, where these infections are endemic. This study aimed to assess the prevalence and factors associated with enteroparasitosis in patients with chronic urticaria. This is a cross-sectional, analytical and observational study, carried out with a sample of 41 patients with chronic urticaria, followed up at a reference service in the state of Paraiba. Parasites were investigated by parasitological examination of feces, and the weight-of-evidence statistical model was used to explain the occurrence of enteroparasitosis and support decision-making. The prevalence of enteroparasitosis was 38.7% of participants. The most prevalent enteroparasites were enterocomal, with the protozoan Endolimax nana present in 81.25% of the positive samples. The variables that showed evidence of explaining the occurrence of enteroparasitosis were: family nucleus, use of corticosteroid therapy, receiving a family grant, number of rooms in the home, treatment of drinking water and living in a rural area. The results reinforce the importance of testing for parasitic infections in patients with chronic urticaria, especially those living in poor housing conditions and using corticosteroids, and the use of appropriate methods is essential to minimize false negative results.